2020
DOI: 10.1002/suco.201900563
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐plane flexural behavior of full precast concrete hollow‐core slabs with lateral joints

Abstract: This paper proposed a new lateral joint to connect precast concrete hollow‐core slabs (PCHSs) and increase their structural assembly efficiency. The main sensitive parameters are the longitudinal ribs and the number of proposed joints. Out‐of‐plane bending performance tests were conducted on four PCHSs with lateral joints (PCHS‐LJs) to study the effects of the main sensitive parameters on the mechanical properties and failure modes of the PCHS‐LJs. The test results showed that there is no obvious relative slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Structure [47,53] In addition to lateral loads, connection systems should meet other performance criteria. In the study by Jiang and Zhang [51], the out-of-plane bending performance of a PC hollow core slab with a suggested lateral joint was tested. From the test results, the relationships between the performance and effects of the rib of the slab and the number of joints on the crack of the slab were identified.…”
Section: Considerations In Design Phase For Osc Project 41 Considerat...mentioning
confidence: 99%
“…Structure [47,53] In addition to lateral loads, connection systems should meet other performance criteria. In the study by Jiang and Zhang [51], the out-of-plane bending performance of a PC hollow core slab with a suggested lateral joint was tested. From the test results, the relationships between the performance and effects of the rib of the slab and the number of joints on the crack of the slab were identified.…”
Section: Considerations In Design Phase For Osc Project 41 Considerat...mentioning
confidence: 99%
“…The simulations show that changing the friction coefficient, the grade of the cast-in-place concrete, and the grade of the concrete used with shear keys had very little effect on the mechanical properties of BCSWSKs, mostly <3.2%, and their load-displacement curves almost coincided, but changing the other parameters had clearly observable effects, as shown in Figures 21-23. Figure 21 shows the load-displacement curves of BCSWSKs for different numbers of shear key columns (Z = 3,4,6,8,9). Figure 21 and Table 2 show that the bearing capacity increased as the number of shear key columns increased.…”
Section: Parameter Influencementioning
confidence: 99%
“…The shear keys can also be connected to temporary I-beams to increase the stiffness of the PBSs to realise support-free construction (Figure 2b). There are large bodies of systematic research on each [3][4][5][6][7][8][9][10][11]. Liu et al [12] confirmed the practicality of using STLSs by empirical testing; Ma et al [13] investigated its mechanical properties in construction and in service by testing and numerical modelling; Zhao et al [14] analysed the influence of parameters, such as concrete strength and truss height and diameter, on the mechanical properties of STLSs using ANSYS software; and Cheng [15] developed a short-term stiffness model for STLSs from theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a reliable construction building material, concrete could meet the requirements of demanding construction conditions, different shaped structural components, and harsh environment for its mature construction technologies and superior properties [1][2][3]. With the increasing industrialization and commercialization of civil engineering, the requirements of buildings have converted to large-span structures, which present new challenges to the concrete floor system [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…rough the design and construction of a real-life project, the feasibility of this new floor system was verified. Other kinds of novel floor systems, i.e., PK prestressed composite slab floor system [15], the assembled monolithic hollow-ribbed floor [16], prefabricated PC floor system [17], and other new systems [18][19][20][21][22], were all investigated, and the results were satisfactory. is paper presents a new type of floor system, which consists of hollow precast panels, self-thermal-insulation infills, joints with welded reinforcement, and cast-in-situ concrete beams.…”
Section: Introductionmentioning
confidence: 99%